Are there health benefits of being unionized in late career? A longitudinal approach using HRS. Issue 9 (28th June 2018) - Wels, Jacques
Abstract : Objective: To assess whether unionization prevents deterioration in self‐reported health and depressive symptoms in late career transitions. Methods: Data come from the Health and Retirement Study ( N  = 6475). The change in self‐perceived health (SPH) and depressive symptoms (CESD) between wave 11 and wave 12 is explained using an interaction effect between change in professional status from wave 10 to wave 11 and unionization in wave 10. Results: The odds of being affected by a negative change in CESD when unionized are lower for unionized workers remaining in full‐time job (OR:0.73, CI95%:0.58;0.89), unionized full‐time workers moving to part‐time work (OR:0.66, CI95%:0.46;0.93) and unionized full‐time workers moving to part‐retirement (OR:0.40, CI95%:0.34;0.47) compared to non‐unionized workers. The same conclusion is made for the change in SPH but with odds ratios closer to 1. Conclusion: The reasons for the associations found in this paper need to be explored in further research.